Pengaruh Media Pembelajaran Multiply Cards terhadap Hasil Belajar Matematika Siswa Kelas IV SD Negeri Beroanging - Despryanto Despryanto; Sukmawati Sukmawati; Ernawati Ernawati (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
The study focuses on the influence of the Multiply Cards learning media on the mathematics learning outcomes of fourth-grade students at SD Negeri Beroanging. The main issue in this research is whether the Multiply Cards learning media affects the mathematics learning outcomes of fourth-grade students at SD Negeri Beroanging. This research is a quantitative study using an experimental method with a "One Group Pretest Posttest Design." The research population consists of all fourth-grade students at SD Negeri Beroanging. The sampling technique employed is probability sampling, specifically cluster random sampling, where the sample is randomly taken from classes IV A, B, and C at SD Negeri Beroanging. Consequently, the sample obtained is class IV B, consisting of 31 students, comprising 18 girls and 13 boys. Data collection is conducted through testing and observation techniques. The collected data is analyzed using descriptive and inferential statistical analysis.Based on the data analysis results, the effect of the Multiply Cards learning media on the mathematics learning outcomes of fourth-grade students at SD Negeri Beroanging is found to be 5.23. This calculated t-value (tHitung) can be compared with the table t-value (tTabel) for db = N-1, where N=31, thus db = 31–1 = 30 at a significance level of 0.05. The tHitung = 5.23 and tTabel = 1.697. Therefore, tHitung > tTabel. The comparison of the pretest and posttest results indicates that the tHitung value of 5.23 is greater than the tTabel value of 1.697. This shows that the proposed research hypothesis is accepted. The hypothesis is tested using a t-test statistic, indicating that the use of the Multiply Cards learning media has a significant effect on the mathematics learning outcomes of fourth-grade students at SD Negeri Beroanging.